The impact of HRM practices on OCB-I and OCB-O, with mediating roles of organizational justice perceptions: Moderating roles of gender - Veseli Artan; Çetin Fatih (Journal of Economics and Management)
Aim/purpose – The purpose of this study is to investigate the impact of HRM practices on OCB-I (altruism and courtesy) and OCB-O (sportsmanship, conscientiousness, and civic virtue) by examining the mediating role of organizational justice perceptions (i.e., distributional, procedural, and interactional justice) and the moderating role of gender.